Psychosocial Disabilities in Patients with Schizophrenia - MA Goreishizadeh; A Mohagheghi; S Farhang; L Alizadeh (Tehran University of Medical Sciences, 2012)
Background: This study aimed at revaluating the psychosocial disabilities in schizophrenic patients. Methods: In an analytic-descriptive setting, schizophrenic patients were evaluated in Razi University Hospital during a one-year period (2009-10). The study group consisted of male and female patients aged 18-65 years, with the onset of disease for a minimum of 2 years and at least one psychological hospitalization in their medical record. The demographic data, as well as the results of the SANS, SAPS, GARF and SOFAS questionnaires were determined in each patient. Results: Two hundred and eight patients, 53 females, and 155 males with the mean age of 36.96±11.55 (18-65) years were enrolled. Vocational, educational, social, familial, and self-hygiene related disabilities were seen in 63.5%, 21.2%, 93.8%, 13.9%, and 48.1% of the patients, respectively. Totally, psychosocial disabilities were reported in 98.1% of these patients. The mean age of the patients with educational or social disabilities was lower. Vocational problems were more common in male patients. Familial and social disabilities were positively related to the severity of positive and negative symptoms, with the predominance of the latter. Positive and negative symptoms were more frequent in patients with social and self-care related disabilities, respectively. The duration of the disease was significantly correlated with the positive symptoms and familial-social disabilities. Conclusion: The current study described the high prevalence of psychosocial disabilities in patients with schizophrenia and may have implications for public health interventions.